Gambaran Faktor-Faktor yang Mempengaruhi Ibu Hamil dalam Kepatuhan Konsumsi Multiple Micronutrient Supplement (MMS) di Puskesmas Ngaliyan Kota Semarang - Andin Noor Oktavianingsih; Sri Wahyuni; Hanifa Andisetyana Putri (Journal of Midwifery Science: Basic and Applied Research, 2026)
Anemia among pregnant women remains a significant public health problem in Indonesia, with a prevalence of 27.7%. Multiple Micronutrient Supplement (MMS) is an important intervention for anemia prevention; however, its effectiveness largely depends on pregnant women’s adherence to its consumption. At Ngaliyan Public Health Center, 301 anemia cases were recorded in 2023 and 33 cases in early 2025, indicating that anemia persists despite the provision of supplementation. This study aimed to describe the factors influencing adherence to MMS consumption among pregnant women, including education level, occupation, income, medical history, sources of information, and adherence behavior. This study employed a descriptive quantitative design with a cross-sectional approach. The study population consisted of third-trimester pregnant women who attended antenatal care at Ngaliyan Public Health Center. A total sampling technique was applied, involving 65 respondents. Data were collected using a structured questionnaire assessing adherence indicators, including dosage, timing, frequency, and method of MMS consumption. The results showed that most respondents had a moderate education level (46.1%), were unemployed (61.5%), and had a family income above the Regional Minimum Wage of Semarang City (69.2%). Nearly all respondents had no medical history (98.5%), and all respondents received information about MMS from healthcare workers (100%). Overall adherence to MMS consumption was categorized as good. These findings indicate that education level, income, and access to information from healthcare workers play an important role in supporting pregnant women’s adherence to MMS consumption. Keywords       : Compliance, Pregnant Women, Multiple Micronutrient Supplement (MMS), Anemia.